Association of DGAT1 With Cattle, Buffalo, Goat, and Sheep Milk and Meat Production Traits - Khan, Muhammad Zahoor; Ma, Yulin; Ma, Jiaying; Xiao, Jianxin; Liu, Yue; Liu, Shuai; Khan, Adnan; Khan, Ibrar Muhammad; Cao, Zhijun (Frontiers in Veterinary Science, 2021)
Milk fatty acids are essential for many dairy product productions, while intramuscular fat (IMF) is associated with the quality of meat. The triacylglycerols (TAG) are the major components of IMF and milk fat. Therefore, understanding the polymorphisms and genes linked to fat synthesis is important for animal production. Identifying quantitative trait loci (QTL) and genes associated with milk and meat production traits have been the objective of various mapping studies in the last decade. The QTLs on chromosome 14, 15 and 9 have been found to be associated with milk and meat production traits in cattle, goat, buffalo and sheep respectively. The DGAT1 gene has been reported on chromosome 14, 15 and 9 in cattle, goat, buffalo and sheep respectively. Being a key role in fat metabolism and TAGs synthesis, the diacylglycerol O-acyltransferase 1 (DGAT1) has got considerable attention in animal milk and meat production. Several polymorphisms have been documented in DGAT1 in various animal species including cattle, buffalo, goat and sheep for their association with meat and milk production traits. Keeping in view the important role of DGAT1 in animal production, the current review article was designed to highlight the major development on DGAT1 effect on milk and meat production traits in cattle, buffalo, sheep and goat.